2022
DOI: 10.34172/ijhpm.2022.6659
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluating Our Knowledge of Health System Resilience During COVID-19: Lessons From the First Two Years of the Pandemic

Abstract: Background: Health challenges like coronavirus disease 2019 (COVID-19) are becoming increasingly complex, transnational, and unpredictable. Studying health system responses to the COVID-19 pandemic is an opportunity to enhance our understanding of health system resilience and establish a clearer link between theoretical concepts and practical ideas on how to build resilience. Methods: This narrative literature review aims to address four questions using a health system resilience framework: (i) What do we unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 93 publications
2
7
0
Order By: Relevance
“…These results also add further credence to the importance of governance in resilience to health shocks 30. A growing body of scholarship argues for the central role of leadership and coordination in defining national-level COVID-19 responses; our findings emphasise the additionally critical role of subnational leadership and coordination 6 31–35. Capable leadership is likely especially important; in our qualitative results, local leadership was described as enabling other resilience capabilities by supporting the LGA team in carrying out response strategies (eg, by steering coordination bodies, coordinating local funding, and motivating PHC planners and health professionals to engage in demand-side adaptations to drive service utilisation).…”
Section: Discussionsupporting
confidence: 65%
“…These results also add further credence to the importance of governance in resilience to health shocks 30. A growing body of scholarship argues for the central role of leadership and coordination in defining national-level COVID-19 responses; our findings emphasise the additionally critical role of subnational leadership and coordination 6 31–35. Capable leadership is likely especially important; in our qualitative results, local leadership was described as enabling other resilience capabilities by supporting the LGA team in carrying out response strategies (eg, by steering coordination bodies, coordinating local funding, and motivating PHC planners and health professionals to engage in demand-side adaptations to drive service utilisation).…”
Section: Discussionsupporting
confidence: 65%
“…The majority of HSR research in these contexts has been conducted in response to infectious disease outbreaks on government health systems, rather than explicitly investigating the compounding effects of multiple stressors (economic, societal, political) that determine fragility and instability. A recent review on the responses to acute shocks in FCAS conducted by Thu et al found similar results, with 42 of the 60 studies focused on infectious disease triggers [ 33 ].While some of the findings from FCAS echo what is described in LMICs in general, other results emerged as new and specific to these contexts [ 78 ].…”
Section: Discussionmentioning
confidence: 87%
“…In this sense, knowledge and awareness appear to be overlooked dimensions for HSR. The fundamental role of information sharing and establishing feedback loops within and across systems has been recognised as a key determinant of HSR during the COVID-19 pandemic [ 78 ]. In FCAS, identifying potential sources of information needs to be a diverse and inclusive process because of the multiplicity of actors involved, including communities and non-state actors [ 2 , 29 , 54 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The observation that staff in several NGOs reported limited strategic oversite and mixed messaging reflects findings from global reviews on conflicting leadership strategies and funding priorities in LMICs during the pandemic [ 57 ]. Evidence was also not identified on health system resilience and there is a need for more research on this in crisis-affected settings to support more effective health system responses, leadership and decision-making [ 58 , 59 ]. Studies with crisis-affected populations, such as in Eastern Democratic Republic of Congo, have highlighted how violence, mobility restrictions, and resource availability impede access to services.…”
Section: Discussionmentioning
confidence: 99%